Applications Of Gravity Beneficiation In Gold Hydrometallurgical Systems - D. Erik Spiller (Society for Mining, Metallurgy & Exploration, 1984)
Introduction The recovery of precious metals from ore can generally be accomplished using either gravity concentration, flotation, and/or hydrometallurgical (leaching) techniques. The objective of this paper is to show why gravity concentration can be an important part of recovery systems which employ leaching as the primary unit operation. A brief discussion of modern gravity concentration equipment is also presented.